FAKTOR PENENTU TERJADINYA MANAJAMEN LABA PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - Amilin - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
TRACTThis study attempted to find out whether the company size and the leverage have anysignificant effect on earning management. The agency theory as a basic theory in this study. Thesample firms used in this study were all the manufacture companies listed on Indonesian StockExchange for period on 2005-2009. There were 19 companies that acquired by using purposivesampling method. The multiple regression analysis used in this study. Findings confirmed thatcompany size and leverage have simultaneously and significantly effect on earning management.Company size and leverage have positive partially significant influence on earning management.